Mitral Valve Repair for Functional Mitral Regurgitation-Description of A New Technique and Classification System - Chiricolo, Antonio; Lee, Leonard Y (Cardiology and Cardiovascular Medicine, 2017)
Herein is reported a case of a 59-year-old male with history of non-compliance, insulin dependent diabetes and congestive heart failure admitted with recurrent symptoms of chest pain with exertion, shortness of breath, and lower extremity edema. Work up including cardiac catheterization and echocardiography revealed severe triple vessel coronary artery disease, severely depressed left ventricular (LV) ejection fraction (EF) of 15% with an enlarged LV cavity (>7.0 cm internal dimension during diastole), severe functional mitral regurgitation (MR; Carpentier type IIIb) [1] and pulmonary artery hypertension (PAP 60/30). A cardiac MRI was obtained to assess viability. Although much of the LV was non-viable, there were patchy areas of viability throughout the LV. Given his relatively young age and the results of the viability, the patient was taken to the operating room for coronary artery bypass (left internal mammary artery to the left anterior descending artery, saphenous vein graft to the obtuse marginal number 1, and saphenous vein graft to the right posterior descending artery), LV assist device standby, and a complex mitral valve repair with release of secondary chordae to the anterior and posterior leaflets, reduction annuloplasty with a 28 mm rigid Carpentier-Edwards Physio annuloplasty ring (Edwards Lifesciences, Irvine, CA, USA) and an Alfieri stitch [2] with 5-0 polypropylene suture to approximate A2 to P2. At the termination of the procedure, there was no mitral regurgitation, preserved LV EF of 15-20%. After 7-day recovery in the hospital the patient was discharged to home and a follow up echocardiogram was performed 6 months post procedure, which demonstrated an LV EF of 15-20% and no mitral regurgitation (no change in the mitral valve over several months). In addition, the patient reported marked improvement in his symptoms with improved exercise tolerance despite the persistently poor ventricular function.